2023
DOI: 10.3390/ma16031018
|View full text |Cite
|
Sign up to set email alerts
|

Carbonization of MOF-5/Polyaniline Composites to N,O-Doped Carbon/ZnO/ZnS and N,O-Doped Carbon/ZnO Composites with High Specific Capacitance, Specific Surface Area and Electrical Conductivity

Abstract: Composites of carbons with metal oxides and metal sulfides have attracted a lot of interest as materials for energy conversion and storage applications. Herein, we report on novel N,O-doped carbon/ZnO/ZnS and N,O-doped carbon/ZnO composites (generally named C-(MOF-5/PANI)), synthesized by the carbonization of metal–organic framework MOF-5/polyaniline (PANI) composites. The produced C-(MOF-5/PANI)s are comprehensively characterized in terms of composition, molecular and crystalline structure, morphology, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 72 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…The cMOF.E and cMOF.EBc samples show mean particle sizes of 145 and 139 nm, respectively, whil similar value is obtained for the cMOF sample, 132 nm. These differences in the me particle size and particle size distribution of the tested materials may be associated w the more hydrophilic surface of cMOF.ESb, indicated by thermogravimetric measu ments [29], and its better dispersibility in water, in comparison to the cMOF.EB sample…”
Section: Particle Sizementioning
confidence: 99%
See 2 more Smart Citations
“…The cMOF.E and cMOF.EBc samples show mean particle sizes of 145 and 139 nm, respectively, whil similar value is obtained for the cMOF sample, 132 nm. These differences in the me particle size and particle size distribution of the tested materials may be associated w the more hydrophilic surface of cMOF.ESb, indicated by thermogravimetric measu ments [29], and its better dispersibility in water, in comparison to the cMOF.EB sample…”
Section: Particle Sizementioning
confidence: 99%
“…Two forms of PANI, synthesized by the oxidative polymerization of aniline with ammonium peroxydisulfate (APS), were used for MOF-5/PANI composites prepa-ration: conducting emeraldine salt, ES, synthesized in the solution of HCl (0.2 M aniline hydrochloride, 0.25 M APS) and nonconducting emeraldine base, EB, synthesized in water without added acid (0.2 M aniline, 0.25 M APS) and dedoped by an excess of alkali, according to refs. [28,29]. The composite is denoted as MOF.ESb, with 77 wt.% MOF-5 content, was prepared by mechanical mixing of MOF-5 and ES components in the presence of chloroform [28].…”
Section: Materials Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ polymerization, however, requires the addition of several chemicals and is a time-consuming and complicated process. Savic et al 35 reported C-MOF-5/polyaniline composites by combining MOF-5 and polyaniline in the emeraldine salt state, followed by carbonization. Unfortunately, the carbonization of conductive polymers can lead to a loss of their electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three-dimensional carbon electrodes have been fabricated owing to their porous networks that enhance electron transport, contributing to electrochemical stability. Metal–organic frameworks (MOFs) have attracted particular attention owing to their high micropore volume and large surface area (>1000 m 2 g –1 ), which potentially generate electrochemically active sites. Among them, the zeolitic imidazolate framework (ZIF)-8 has widespread applications because of its stable structure and robustness. , ZIF-8 carbonization enables the fabrication of three-dimensional carbon electrodes with improved electrical conductivity while preserving the nanoporous networks. As ZIF-8 contains heteroatoms (such as N) in the ligand, the carbon resulting from the organic ligand is doped with heteroatoms, which facilitates rapid electron transport to the redox reaction by the pseudocapacitive effect. Additionally, the evaporation of Zn leads to the formation of micropores, rendering porous carbon materials with excellent electrical conductivity and a high specific surface area. , The specific surface area of carbonized ZIF-8 (C-ZIF-8) can be adjusted according to the original particle size of ZIF-8 . For the aforementioned materials to be successfully applied in various energy storage system applications, C-ZIF-8 requires improved electrical conductivity and electrochemical and physical stability.…”
Section: Introductionmentioning
confidence: 99%